2021
DOI: 10.1590/0074-02760200513
|View full text |Cite
|
Sign up to set email alerts
|

Transmission-blocking compound candidates against Plasmodium vivax using P. berghei as an initial screening

Abstract: BACKGROUND Different strategies for improvement of malaria control and elimination are based on the blockage of malaria parasite transmission to the mosquito vector. These strategies include the drugs that target the plasmodial sexual stages in humans and the early developmental stages inside mosquitoes.OBJECTIVES Here we tested Malaria Box compounds in order to evaluate their activity against male and female gametocytes in Plasmodium berghei, mosquito infection in P. vivax and ookinete formation in both speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Overall, our study showed that, in ex vivo cultures, gametocytes were viable and infectious for up to 48 h, with significant differences from 12 h. Recently, our group has evaluated methods for testing transmission blocking compound candidates (Fabbri et al, 2021) and, despite being well used, a direct membrane feeding assay (DMFA) can present limitations such as the lack of an exposure time capable of evaluating possible gametocidal activity. In our analysis, we observed that gametocytes cultured within 6 h can be used initially to screen for new agents with anti-gametocyte action and, as such, this allows direct validation of infectious gametocytes.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Overall, our study showed that, in ex vivo cultures, gametocytes were viable and infectious for up to 48 h, with significant differences from 12 h. Recently, our group has evaluated methods for testing transmission blocking compound candidates (Fabbri et al, 2021) and, despite being well used, a direct membrane feeding assay (DMFA) can present limitations such as the lack of an exposure time capable of evaluating possible gametocidal activity. In our analysis, we observed that gametocytes cultured within 6 h can be used initially to screen for new agents with anti-gametocyte action and, as such, this allows direct validation of infectious gametocytes.…”
Section: Discussionmentioning
confidence: 90%
“…However, current knowledge regarding gametocytes is the result of well-established in vitro studies of Plasmodium falciparum and experiments with Plasmodium berghei in rodents ( Ngotho et al., 2019 ). In P. vivax , membrane-feeding assays (MFA) have been used to investigate the period of viability of gametocytes under different conditions ( Vallejo et al., 2016 ; Pereira-Silva et al., 2021 ), the biological characteristics and dynamics ( Vallejo et al., 2016 ) and candidates for transmission blocking ( Pinilla et al., 2018 ; Fabbri et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to widespread resistance to current antimalarial drugs, there is an urgent need for research on effective, safe, and affordable antimalarial compounds, since the main tool for malaria control is chemotherapy ( Na-Bangchang and Karbwang, 2013 ; Fabbri et al., 2021 ). Furthermore, a drug must have both anti-recrudescence and blood schizontocidal activity, besides acting in gametocytes stages and/or sporogonic forms with minimal side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Oocyst infection intensity was calculated by dividing the total number of oocysts by the total number of infected mosquitoes. The inhibition percentage of each compound was calculated as previously described ( Fabbri et al., 2021 ). To evaluate the differences in the oocyst number among the groups was used Kurskal-Wallis test with Dunn’s multiple comparison test.…”
Section: Methodsmentioning
confidence: 99%
“…The DMFA was conducted according Fabbri et al., 2021 with few modifications. Three different sets of DMFA experiments were performed.…”
Section: Methodsmentioning
confidence: 99%